Caring for the Weeds: A vegetalised approach to urban activism and participatory art - Bobei, Irina Anca (Journal of Ecohumanism, 2024)
Care is a slippery notion, especially in times of ecological upheavals when a seemingly benign metaphor could have the power to instigate a new social, political or environmental change. Due to its instrumentalisation in theoretical and practical endeavours as a gendered concept, caring as environmental consciousness loses its potential to facilitate active change in day-to-day urban activities and risks becoming a violent tool trapped in patriarchal narratives (Macgregor, 2007). This article draws from the interdependencies between artistic expressions of urban activism and plant specificities and agencies through a vegetalised approach (Myers, 2021) to interspecies entanglements. The main section investigates plant/human relationships from an ecofeminist perspective, by offering an overview of the interweavings of public gardening, the representation of wastelands and how collective ‘response-ability’ (Haraway, 2016) is reformulated in the context of caring for informal urban spaces. The practice and artistic interventions of Sophie Leguil and Lois Weinberger will unravel how tending to marginalized plants facilitates an empowering caring perspective, producing speculative narratives to overcome anthropocentric and violent views. By invoking the concept of plant-thinking (Marder, 2013), the second part of the article will focus on other artistic expressions where human and vegetal subjectivities co-evolve, revealing a way to mix the economy of grassroots movements with the politics of cosmopolitan environmental consciousness, encouraging action across differences, intra- and among species. The article concludes by showing the transformative potential of Dagna Jakubowska’s installation Weeds (2021) and Ellie Irons’ performative laboratory Feral and Invasive Pigments (2012 - ongoing) to encourage new visions of caring for environment as a political act.